EEG: Applications for Sport and performance - Part one - Thompson, T.; Steffert, T.; Ros, T.; Leach, J.; Gruzelier, J. (EWF Scientific Magazine, 2019)
EEG represents a useful methodological tool in understanding cortical processes that underlie performance in sporting and non-sporting domains. Although EEG lacks the spatial resolution of more expensive methods such as MEG or fMRI, it offers excellent temporal resolution and with advances in wireless hardware and equipment portability, allows a freedom of movement almost impossible to achieve with other neuroimaging technologies. Recording EEG during motion does present a number of problems with respect to obtaining 'clean' cerebral data. However, careful attention to proper methodological practices and developments in hardware and computational processing models offer a promising means of minimising, if perhaps not entirely eradicating, these problems.